A Systematic Review of Interventions—Does Invisalign Move Teeth as Effectively as Orthodontic Fixed Appliances? - Mohammad Khursheed Alam; Mohammed Awawdeh; Nora Alhazmi; Khalid A. Abalkhail; Kiran Iyer; Huda Abutayyem; Haytham Jamil Alswairki; Mohammad Younis Hajeer (Scientifica, 2024)
Registration and Protocol: Registration was done in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) standards (CRD42023405593). The research protocol was created to meet the goals and was properly filed with PROSPERO; however, it has not been prospectively registered.